Language teachers and crowdsourcing insights from a cross-European survey - Arhar Holdt, Špela; Zviel-Girshin, Rina; Gajek, Elżbieta; Durán-Muñoz, Isabel; Bago, Petra; Fort, Karën; Hatipoglu, Ciler; Kasperavičienė, Ramunė; Koeva, Svetla; Lazić Konjik, Ivana; Miloshevska, Lina; Ordulj, Antonia; et al. (2020)
The paper presents a cross-European survey on teachers and crowdsourcing. The survey examines how familiar language teachers are with the concept of crowdsourcing and addresses their attitude towards including crowdsourcing into language teaching activities. The survey was administrated via an online questionnaire and collected volunteers’ data on: (a) teachers’ experience with organizing crowdsourcing activities for students/pupils, (b) the development of crowdsourced resources and materials as well as (c) teachers’ motivation for participating in or employing crowdsourcing activities. The questionnaire was disseminated in over 30 European countries. The final sample comprises 1129 language teachers aged 20 to 65, mostly working at institutions of tertiary education. The data indicates that many participants are not familiar with the concept of crowdsourcing resulting in a low rate of crowdsourcing activities in the classroom. However, a high percentage of responding teachers is potentially willing to crowdsource teaching materials for the language(s) they teach. They are particularly willing to collaborate with other teachers in the creation of interactive digital learning materials, and to select, edit, and share language examples for exercises or tests. Since the inclusion of crowdsourcing activities in language teaching is still in its initial stage, steps for further research are highlighted.
U radu je predstavljeno europsko istraživanje o nastavnicima i gomilizaciji (engl. crowdsourcing). U istraživanju je ispitano koliko su nastavnici jezika upoznati s konceptom gomilizacije te su ispitani njihovi stavovi o uključivanju gomilizacije u aktivnosti poučavanja jezika. Istraživanje je provedeno s pomoću mrežnog upitnika, a prikupljani su podatci o: (a) iskustvu nastavnika u organizaciji gomilizacijskih aktivnosti s učenicima/studentima, (b) razvoju gomilizacijskih resursa i materijala, kao i (c) motivaciji nastavnika za sudjelovanjem u gomilizaciji i upotrebi njezinih aktivnosti. Upitnik je distribuiran u više od 30 europskih zemalja. Uzorak obuhvaća 1129 nastavnika jezika u dobi od 20 do 65 godina, koji rade uglavnom u institucijama tercijarnog obrazovanja. Podatci upućuju na to da ispitanici nisu upoznati s konceptom gomilizacije, zbog čega je niska stopa gomilizacijskih aktivnosti u učionici. Međutim, velik je postotak nastavnika koji su voljni sudjelovati u gomilizaciji kako bi se razvili obrazovni sadržaji za jezike koje poučavaju. Posebno su voljni surađivati s drugim nastavnicima u stvaranju interaktivnih digitalnih obrazovnih sadržaja te odabirati, uređivati i dijeliti jezične primjere za vježbe i testove. Budući da je uključivanje gomilizacijskih aktivnosti u poučavanje jezika još u povojima, istaknuti su koraci za daljnja istraživanja.
Bibliografske bilješke uz tekst ; bibliografija: str. 26-27.
Summary ; Sažetak.
Keywords: Jezici -- Poučavanje jezika -- Nastavnici -- Gomilizacija -- Crowdsourcing -- Jezična infrastruktura